Struktur Komunitas Padang Lamun di Perairan Kepulauan Waisai Kabupaten Raja Ampat Papua Barat - Muh Haidir Ansal (Jurnal Ilmu Alam dan Lingkungan, 2017)
The research about Community structure of seagrass was conducted in the waters of Waisai, South Waigeo District, Raja Ampat, West Papua. The aim of this study was to determine the community structure of seagrass beds found in the waters of the Waisai archipelago, Raja Ampat, West Papua using quadrant transect method. Data of community structure were obtained at 3 stations that were station I  in the countryside of Waisai (Post AL), station II in the Resort Waiwo (Waiwo Dive Center) and Station III in Saporkren village near residential areas. The results of this study discovered seven species of seagrass; Enhalus acoroides, Halophila decipiens, H. ovalis, Thalassia hemprichii, Cymodocea rotundata, Halodule pinifolia, Syringodium isoetifolium in all stations. Cymodocea rotundata had the highest importance value index (IV) which amounted to 79.22%, 161.15% and 134.68% in each station, respectively. While Syringodium isoetifolium had the lowest importance value index, respectively 00,00%, 6.91% and 7.80% in each station. Seagrass of Waisai waters had clumped distribution patterns. The seagrass Cymodocea rotundata is the most dominant seagrass species and influential in the community and the results of environmental parameters, pH, temperature, salinity, substrate, measured in research location are still feasible and great for the growth of seagra